The Effect of Work Discipline and Motivation to Work Productivity on Production Division Employee of PT X - Shinutama, Betha Pramesthi; Agung Wahyu Handaru; Christian Wiradendi Wolor (JURNAL DINAMIKA MANAJEMEN DAN BISNIS, 2021)
The purpose of this study is: To find out 1) To analyze the description of work discipline, motivation on employee productivity at PT X 2) To analyze the effect of work on employee productivity at PT X. 3) To analyze the influence of motivation on employee productivity at PT X. This research was conducted on 95 employees of the PT X on Jl. Manggul Jaya, Bantargebang. 4) To determine work discipline and motivation to predict employee productivity at PT X on Jl. Manggul Jaya, Bantargebang. Data collection techniques using survey methods by distributing questionnaires which are then processed with the SPSS 25 program. This research uses descriptive and explanatory analysis. The result obtained from the regression show that there is a positive and significant influence between Work Discipline and Motivation to Work Productivity. The research model of Work Discipline and Motivation can predict Work Productivity on production division employee of PT X which on Jl. Manggul Jaya, Bantagebang Bekasi, with a value of Fcount > Ftable (61,471> 3,10) and significance (0,000 < 0,05).